A Cross-Sectoral Comparison of Prevalence and Predictors of Symptoms of Depression Over Time Among Older Adults in Ontario, Canada. (January 2021) - Neufeld, Eva; Freeman, Shannon; Spirgiene, Lina; Horwath, Urszula
Objectives: Late-life depression, a common mental health issue, poses a significant burden of illness globally. We investigated factors associated with symptoms of depression among older adults across 3 health sectors in Ontario, Canada. Method: Electronic health assessment data on older adults aged 60 years+ in home care (HC; N = 359 217), long-term care (LTC; N = 125 496), and palliative care (PC; N = 29 934) were examined. Change in symptoms of depression, measured using the interRAI Depression Rating Scale (DRS), over time was examined, including predictors of the development of depression. Results: At baseline, symptoms of depression were observed in 19.1% (HC), 24.2% (LTC), and 11.9% (PC). This increased to 20.6% (HC), 33.8% (LTC), and 13.2% (PC) at follow-up. For most older adults, DRS scores remained the same across sectors over time. Three independent variables emerged consistently across sectors as the main risk and protective factors for symptoms of depression. Conclusion: Although variations in the risk and protective factors for late-life depression were demonstrated across each sector, some commonalities emerged including unmanaged pain, symptoms of depression at baseline, social connectedness, and activity.